2005
DOI: 10.1097/01.pas.0000157295.93914.3b
|View full text |Cite
|
Sign up to set email alerts
|

Columnar Cell Lesions of the Breast: The Missing Link in Breast Cancer Progression?

Abstract: Columnar cell lesions (CCLs) of the breast are a spectrum of lesions that have posed difficulties to pathologists for many years, prompting discussion concerning their biologic and clinical significance. We present a study of CCL in context with hyperplasia of usual type (HUT) and the more advanced lesions ductal carcinoma in situ (DCIS) and invasive ductal carcinoma. A total of 81 lesions from 18 patients were subjected to a comprehensive morphologic review based upon a modified version of Schnitt's classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
206
0
20

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(247 citation statements)
references
References 26 publications
21
206
0
20
Order By: Relevance
“…Emerging evidence suggests that FEA may have an important role in neoplastic progression in the breast. 18,19 Whereas its ultimate role in breast tumorigenesis remains to be more clearly defined, available observational data have indicated that FEA often coexists with other lesions for which the clinical implications and management considerations are better understood such as ADH, DCIS, invasive carcinoma (particularly tubular carcinoma) and lobular neoplasia. 3,5,22,23 Therefore, the recognition of FEA is of importance for surgical pathologists because this serves as a 'red flag', particularly in core biopsies, for the possible presence of these other lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that FEA may have an important role in neoplastic progression in the breast. 18,19 Whereas its ultimate role in breast tumorigenesis remains to be more clearly defined, available observational data have indicated that FEA often coexists with other lesions for which the clinical implications and management considerations are better understood such as ADH, DCIS, invasive carcinoma (particularly tubular carcinoma) and lobular neoplasia. 3,5,22,23 Therefore, the recognition of FEA is of importance for surgical pathologists because this serves as a 'red flag', particularly in core biopsies, for the possible presence of these other lesions.…”
Section: Discussionmentioning
confidence: 99%
“…7,14,[16][17][18][19] In fact, CCLs with cytologic atypia were initially recognized by Azzopardi as a form of DCIS that he designated 'clinging carcinoma'. 6,7,20 Subsequently, De Potter et al separated clinging carcinoma into two subtypes: clinging carcinoma with pleomorphic nuclei and clinging carcinoma with monomorphic nuclei.…”
mentioning
confidence: 99%
“…Micropapillary lesions seem to be an intermediate step between flat epithelial atypia and pure non-micropapillary atypical ductal hyperplasia with 43 and 61% of cancers at surgery. As stated by Simpson,27 there is a morphological and molecular continuum in the degree of proliferation and atypia, and all these lesions are a non-obligate, intermediary step in the development of low-grade carcinomas. Our results confirm this non-obligate continuum since when low-grade ductal carcinoma in situ or infiltrating carcinomas were present at excision, atypical ductal hyperplasia was present at microbiopsy in almost (34 out of 36) or all the cases (n ¼ 10), respectively.…”
Section: Interobserver Reproducibility In the Classification Of Epithmentioning
confidence: 93%
“…[3][4][5][6][7] According to Schnitt and Vincent-Salomon, 1 columnar cell lesions have been grouped into the categories of columnar cell change and columnar cell hyperplasia without or with atypia. Other authors 8 have proposed a subcategorization of columnar cell lesions depending on the presence of architectural and/or cytological atypia. The unifying term 'flat epithelial atypia' has been proposed by the World Health Organization Working Group on the Pathology and Genetics of Tumors of the Breast 9 for columnar cell lesions with low-grade cytological atypia.…”
mentioning
confidence: 99%
“…11 On the other hand, it has been shown that the columnar cell lesions frequently coexist with and show the same genetic alterations of hormonedependent lesions, such as low-grade ductal carcinoma in situ (particularly, micropapillary and cribriform type), lobular intraepithelial neoplasia, and invasive tubular carcinoma. 8,12,13 All these data may be considered for postmenopausal women with a history of columnar cell lesions who are currently receiving or considering for hormone replacement therapy. Moreover, several experts in breast pathology underline that there is an urgent need for large, comprehensive studies describing more accurately the risk of finding malignant diseases after a diagnosis of columnar cell lesions on core biopsy specimens.…”
mentioning
confidence: 99%